Pelatihan Komputer dalam Peningkatan Sumber Daya Manusia Bagi Perangkat Desa - Karim, Abdul; Kusmanto; Suryadi, Sudi; Febriani, Budi (PT. Bangun Harapan Bangsa, 2024)
Computer training plays an important role in improving human resources (HR) of village officials. This research aims to explore the impact of computer training on the ability and work efficiency of village officials. The methods used include surveys before and after training, direct observation, and in-depth interviews. The research results show that computer training significantly improves the technical skills of village officials, which contributes to increased productivity and services to the community. This training also builds self-confidence and increases technological understanding, which is important for adapting to increasingly digital work demands. Thus, computer training has proven to be an effective strategy in developing the human resource capacity of village officials, which, in turn, contributes to overall village progress and development.